Design and on-field testing of wireless sensor network-based air quality monitoring system - Al-Haija, Qasem Abu (Universitas Andalas, 2019)
The wireless sensor networks (WSN) are increasingly implemented in air quality monitoring with real-time and high spatial-temporal resolution. In this context, current work aimed at designing and testing a cost- and energy-efficient WSN-based air quality monitoring system. The system was assembled principally by wireless sensors, solar cells, microcontroller and network communication. In addition, a new circuit for buck-boost converter was implemented for voltage and current regulations. On-field, testing the proposed air quality monitoring system outdoor and indoor showed efficient real-time readings for the concentrations of carbon dioxide (CO2) and total volatile organic compounds (TVOC). Furthermore, it provided data about ambient temperature, relative humidity and air pressure with good accuracy. In conclusion, our results suggest a reliable and scalable WSN-based system for monitoring ambient air quality.